Descriptive representation about transformation of company by using current technologies and tools for analytical processing and evaluation of diverse data - Gabriel Koman; Martin Holubcik; Milan Kubina (Managerial Economics)
Companies are currently producing and processing larger and larger amounts of data that they were not able to effectively process and subsequently use in the management of company pro-cesses in the past. There are several technologies and tools for the analytical processing and evaluation of diverse data, such as the Big Data technology. The Industry 4.0 concept (which is closely linked with the IoT) will bring an enormous growth of produced data into the company sphere. The information value of such data can signifi cantly affect managing and decision-making processes in a company. Here, we can see a synergy between man and technology where each infl uences the other. The purpose of this paper is to support the following statement: in the present business environment, we are facing the transformation of a company that, for effi cient management and decision-making, needs: a) to capture and process all available data; b) to implement new tools into strategic decisions; and c) to integrate data through a single system. This article describes the possibilities of deploying the effi cient use of new technologies (Big Data, Industry 4.0, and IoT) in management.